THE ROLE OF THE PUJAKESUMA ASSOCIATION IN WINNING SIMALUNGUN REGENCY LEGISLATIVE CANDIDATES IN THE 2024 ELECTION: PERAN PAGUYUBAN PUJAKESUMA DALAM PEMENANGAN CALON LEGISLATIF KABUPATEN SIMALUNGUN PADA PEMILU 2024 - Najwa El-Khoir Hasibuan; Elly Warnisyah Harahap (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This article discusses how the role given by the Pujakesuma group, especially in winning legislative candidates in Simalungun Regency, which is a minority area of the Javanese tribe, in the 2024 election. The writing of this journal uses a qualitative method, with data collection techniques in the form of in-depth interviews with figures from the Pujakesuma community, which is accompanied by documentation and literature studies. The analysis technique used is a qualitative descriptive analysis, through references from journals, and books that are then re-analyzed by the author. The findings obtained from this study are that the largest votes obtained from ethnic Javanese were obtained in Bandar Masalam district, which is an area with a majority of ethnic Javanese ethnicity. The Pujakesuma Association played a major role in winning legislative candidates in Simalungun Regency in the 2024 election. This shows that associations that are synonymous with cultural organizations can take an important role in politics. A well-managed cultural realm will create good results in the surrounding environment, including in the political environment.